Integrative Research Syntheses as Sites of Disruption in Literacy Teacher Education. (June 2019) - Lysaker, Judith T.; Handsfield, Lara J.
In this Insight article, we look across the syntheses in this issue to consider how they help readers notice dominant flows and identify sites for disruption within the field of literacy teacher preparation. We first consider the meaning of disruption with respect to the metaphor of flow. We then identify and discuss possible sites of disruption authors of research syntheses create, providing examples from the literature. Finally, we suggest how research syntheses might be framed and crafted for purposes of disrupting the flows of dominant discourses and power structures in the field of literacy teacher preparation.